1990
DOI: 10.1016/0266-7681(90)90092-i
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Thumbs in Children: A Follow-Up Study of 37 Children Below 15 Years of Age

Abstract: 37 patients who had been operated upon for trigger thumb, all below 15 years of age, have been reviewed. 75% of the affected thumbs were on the dominant hand and 25% have bow-stringing of 1-2 mm. without any complaints. All had good results. Unlike other authors, we found that operation done after the third year of age gave full correction of the flexion contracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 6 publications
2
34
0
Order By: Relevance
“…2,7 In summary, our study suggests there may be a higher rate of spontaneous recovery than previously reported. Overall, of those children referred with a trigger thumb 86% had surgical release.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…2,7 In summary, our study suggests there may be a higher rate of spontaneous recovery than previously reported. Overall, of those children referred with a trigger thumb 86% had surgical release.…”
Section: Discussionsupporting
confidence: 47%
“…[1][2][3] The aetiology remains unknown, but three possible causes have been suggested. First, it may be congenital, [4][5][6][7][8] secondly it may result from trauma 9,10 since it is often misdiagnosed as a fracture of the thumb or dislocation of the interphalangeal joint, 1,3,11 and thirdly it may be acquired during the early months of childhood.…”
mentioning
confidence: 99%
“…In 1974, Dinham and Meggitt established treatment guidelines for trigger deformity, specifically, that (1) a trigger deformity that is present at birth should be carefully observed for twelve months, (2) a trigger deformity that is first noticed between the ages of six and thirty months should be observed for six months, and (3) operative treatment should be performed before the age of four years to prevent the creation of residual flexion deformities 3 . However, Skov et al later concluded that the risk of residual flexion deformity was no higher following operations conducted in patients who were more than three years old, supporting initial nonoperative treatment regardless of age 20 . Several conservative approaches to the treatment of pediatric trigger thumb with use of splints have been described by Japanese groups [10][11][12][13] , with success rates ranging from 48% to 89%.…”
Section: Discussionmentioning
confidence: 99%
“…Skov et al noted that the risk of residual deformity was no higher even if operative treatment was performed in patients over the age of three years 20 . Herdem et al reported that a radial deviation deformity had developed in two patients who were managed late (at ten and thirteen years of age) and noted that this deformity is difficult to detect in the flexed thumb but can be seen when the flexion deformity is corrected 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies 5,8 -11 suggest nonoperative treatment for this condition, other studies state that surgery is the recommended treatment for PTT. 1,[12][13][14][15][16][17][18][19][20] Considerable controversy continues to exist regarding the role of surgery in the treatment of PTT.…”
mentioning
confidence: 99%